Socialization of Safety Riding in Reducing Two Wheel Accidents - Chandra, Made (Police Studies Review, 2023)
This research was motivated by the high number of two-wheeled vehicle traffic accidents that occurred in Purwakarta Regency. This traffic problem has disrupted traffic control, which is the responsibility of the Purwakarta Police traffic unit. The Purwakarta Police Traffic Unit is taking preventive measures to reduce the number of two-wheeled vehicle traffic accidents through the Dikyasa Unit by carrying out community education activities in the field of traffic, one of which is safety riding socialization activities, but if it is associated with facts in the field, the number of traffic accidents is still high, an evaluation of the implementation is needed. socialization of safety riding. In this study the authors used a qualitative approach, using field research types, as well as data collection techniques by conducting interviews, observations, and document reviews. The research source used as a reference is related to the implementation of safety riding socialization. The theory used is management theory and communication theory. The concept used is the concept of a two-wheeled vehicle traffic accident, the concept of safety riding and the concept of Kamseltibcar then. The results of the study indicate that the implementation of safety riding socialization requires appropriate management and methods to support these socialization activities. In addition, the communication that occurs in the socialization of safety riding is very important to ensure the delivery of traffic messages to the public, which can be seen from the embedded aspects of traffic discipline in the community of Purwakarta Regency. The conclusion of this study is that the implementation of safety riding socialization carried out by the Purwakarta Police Traffic Unit Dikyasa Unit has not been maximized, this can be seen from the lack of supporting facilities for activities and the lack of innovation in conveying safety riding socialization messages.